The Effect of Low Interest Rates for Islamic Commercial Banks on Student Interest In Saving - Zahra, Nuha Adena; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The Islamic finance industry is one of the most significant factors in the development process, as it contributes to the smooth operation of economic activity. This study aims to determine whether low bank interest affects student interest, especially in Yogyakarta, to save in Islamic banks. The method used in this research is a quantitative approach by distributing questionnaires. Based on data analysis and discussion of the effect of low-interest rates on student interest in saving in Islamic banks, it can be concluded that there is a significant effect. This is a prof from the results of research that has been carried out, where the results of the questionnaire state that low bank interest affects an attractiveness student interest saving in Islamic banks.